Uncovering Legendary Coffee Shops in Pontianak Through Sentiment Analysis - Ilucky Salim; Jimmy Tjen (bit-Tech, 2025)
Nowadays, coffee shops are scattered everywhere offering a variety of unique experiences to attract customers. Despite the rapid emergence of modern coffee shops, certain long-established coffee shops (often referred to as “legendary coffee shops”) continue to thrive and maintain a loyal customer base. The success of legendary coffee shops can be attributed to factors such as signature beverages, distinctive ambiance, and a strong word-of-mouth reputation. Unlike newer establishments that rely heavily on digital marketing, these coffee shops build trust and popularity over time. To further understand their influence, sentiment analysis can be applied to customer reviews of the coffee shops. This study analyzes two legendary coffee shops in Pontianak, namely Aming Coffee Shop and Asiang Coffee Shop to understand the key factors behind their sustainability despite strong competition using Naïve Bayes Method. The best accuracy for testing data at a 50:50 ratio was 76.76%, while training data reached 96.16%. The resulting precision and recall values are 96.16% and 78.81%. This study employs N-gram 3 model to identify the top words of both coffee shops. The findings indicates that both coffee shops are well-known for their signature milk coffee and unique flavor beverages that resonate with the local community. Aming Coffee Shop attracts young customers with affordable prices, while Asiang Coffee Shop maintains its traditional coffee shop ambiance, appealing to customers seeking nostalgia. From these two case studies, it is evident the success of a coffee shop is highly influenced by taste, branding, and customer experience.